Gaining insight into a novice teacher's initial journey through reflective practice. Issue 2 (3rd March 2016) - Naci Kayaoğlu, Mustafa; Erbay, Şakire; Sağlamel, Hasan
Abstract: This small-scale case study conducted in Trabzon, Turkey, aimed at uncovering the attitude of a tertiary-level novice teacher towards reflective practice in English as a foreign-language setting. The data were derived from the pre- and post-study interviews with the novice teacher, her reflective papers on her audio-recorded lessons, her classroom observation notes about the experienced teacher and the informal researcher observations. The researchers' role was to design the process, familiarise the teacher with the focus of reflection, conduct the interviews, analyse and interpret the reflective papers of the teacher. The results show that reflective practice may be challenging in terms of emotions for a novice teacher as it may be hard to confront an outsider's view. The results point to beneficial impact of the self-initiated reflection on the way to teachers' continuous professional development.